GMP-compliant, serum-free cultures preserve therapeutic potential of extracellular vesicles from human mesenchymal stromal cells - Calascibetta, Filippo; Martorana, Annalisa; Lo Pinto, Margot; Carcione, Claudia; D’Arpa, Salvatore; Amico, Giandomenico; Miceli, Vitale; Cuscino, Nicola; Iannolo, Gioacchin; Volpe, Lorenzo; Scilabra, Simone Dario; Conaldi, Pier Giulio; et al. (Frontiers in Cell and Developmental Biology, 2025)
The therapeutic potential of extracellular vesicles (EVs) derived from human mesenchymal stromal cells (MSCs) is limited by the lack of standardized, Good Manufacturing Practice (GMP)-compliant production protocols. This study investigates the effects of MSC-Brew, a commercially available GMP-grade medium, on MSC-derived EVs in comparison to those produced in conventional cultures with DMEM supplemented with 10% fetal bovine serum (FBS). MSCs from adult dermis were successfully isolated and expanded in Brew medium while retaining their characteristic surface marker expression. MSC-EVs derived from Brew cultures met the Minimal Information for Studies of Extracellular Vesicles (MISEV) criteria, including particle size, concentration, marker expression, and minimal inflammatory cytokine content. Notably, Brew-EVs exhibited a significantly higher particle-to-protein ratio compared to EVs produced in FBS-containing cultures, indicating improved purity. Proteomic analysis revealed a largely conserved composition between Brew-EVs and conventionally produced EVs, and microRNA (miRNA) profiling identified only four differentially expressed miRNAs. Brew-EVs were enriched in anti-fibrotic miRNAs and effectively reduced collagen secretion in transforming growth factor (TGF)-β1-activated LX-2 cells, a human hepatic stellate cell line used as a model of liver fibrosis. These findings support MSC-Brew medium as a standardized, serum-free platform for the consistent production of high-quality EVs suitable for therapeutic applications.